Regulating services in the European Union - Hatzopoulos, Vassilis (Oxford : Oxford University Press, 2012)
An overview of services regulation in the EU, tracing its history from early, sector-specific interventions to the complex modern landscape of 'new governance' techniques. It sets the legal developments in their economic context and critiques the varied regulatory methods with which the EU has experimented.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Keywords: Service industries -- Law and legislation -- European Union countries